A Three Phase Matlab Simulink Model of IEEE 57 Bus Power System Network - Gade, VeeraBhadra Chary.; Kotapuri, Mercy Rosalin. (International Journal of Engineering and Technology, 2018)
The Electrical power system, field engineers always strive to design a Real time power system model to anticipate the practical outcomes. The simulation software not only fixes the changes in power system, but also trying to perceive the potential impact of power system before construction. A realistic model of the power system is very essential for the future and present operations. Present, this paper makes center of attention on designing of 3-phase power system network of IEEE 57 bus power system network within the Matlab Simulink module. It supports GUI (Graphical User Interface) based models of power system components, which are used to design a dynamic model of the power system. The present design is based on the test case data and the one line diagram; so that the three-phase model is equivalent to single phase one line diagram. The simulation of this model allows for verification of voltage, current, active power and reactive power of each bus and variation of those parameters with respect to time domain waveform. The present model is also useful for learning the operation of the power system network under Steady state, Transient state and Dynamic state with the application of FACTS, Fuzzy, and ANN etc.